2020
DOI: 10.1111/jcpe.13299
|View full text |Cite
|
Sign up to set email alerts
|

In vivo accuracy of dental magnetic resonance imaging in assessing maxillary molar furcation involvement: A feasibility study in humans

Abstract: Aim To investigate the accuracy and reliability of dental magnetic resonance imaging (dMRI) in assessing maxillary molar furcation involvement (FI). Material and Methods In this prospective study, 22 patients with severe periodontitis underwent cone‐beam computed tomography (CBCT) and dMRI. For 192 furcation entrances, the degree of horizontal FI was assessed by two independent observers on both modalities. Results of dMRI were compared with CBCT (reference modality) to assess the accuracy of dMRI. Cohen's kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…Second, CBCT is superior to current dMRI methods concerning the spatial resolution. In this regard, it should be noted that buccal furcations, which are the narrowest on average (Bower, 1979;Hou et al, 1994), revealed the lowest sensitivity levels for horizontal furcation defects not only in the present NCE-dMRI study but also and in a previous GBCA-dMRI study (Juerchott et al, 2020). This pattern indicates that the sensitivity of dMRI may be reduced for exceptionally narrow furcations due to the lower spatial resolution compared to CBCT.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…Second, CBCT is superior to current dMRI methods concerning the spatial resolution. In this regard, it should be noted that buccal furcations, which are the narrowest on average (Bower, 1979;Hou et al, 1994), revealed the lowest sensitivity levels for horizontal furcation defects not only in the present NCE-dMRI study but also and in a previous GBCA-dMRI study (Juerchott et al, 2020). This pattern indicates that the sensitivity of dMRI may be reduced for exceptionally narrow furcations due to the lower spatial resolution compared to CBCT.…”
Section: Discussionsupporting
confidence: 42%
“…These data are of clinical relevance, as correct furcation diagnosis provides the basis for prognosis estimation and treatment decisions (Avila-Ortiz et al, 2015;Dommisch et al, 2020;Jepsen et al, 2019;Sanz et al, 2020;Walter et al, 2011). Most importantly, the dMRI technique applied in this study does not require the administration of GBCA in contrast to an earlier study (Juerchott et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Since over 20 years, MRI has been commonly used to detect inflammatory processes in various soft and hard tissue compartments, including muscles, joints and bones (Patel et al, 1996; Miller et al, 1997; Sempere et al, 2005). Yet, there are only three studies available focusing on MRI as a method to assess inflammatory processes within the gingival soft tissue in the context of periodontitis (Schara et al, 2009; Newbould et al, 2017; Juerchott et al, 2020). MRI bone sequences are able to generate diagnostic data within osseous structures comparable to those as obtained with CBCT independent from the exposure to ionizing radiation (Cho et al, 2019; Juerchott et al, 2020).…”
Section: Introductionmentioning
confidence: 99%